Self-destruction and its relationship to psychological disorders among university students - Wada’a, Najlaa N. (Al-Adab Journal, 2023)
The aim of the current research is to identify the relationship between self-destruction and psychological disorders and the significance of the differences in the relationship between self-destruction and psychological disorders among students of Al-Mustansiriya University, where self-destruction was defined as a type of self-harm that occurs as a result of psychological trauma, family problems or economic obstacles, and these problems penetrate into the lives of individuals within the community His ability to comprehend the intense thoughts and feelings that it contains, and may be the cause of the death of a close person, physical and psychological torture, abusive relationships, and exposure to repeated abuse are among the reasons through which the adolescent individual resorts to feeling the desire to harm oneself, which accompanies self-destruction, while psychological disorders are known as A behavioral or psychological pattern or syndrome with clinical significance associated with painful symptoms or shortcomings in one or more important areas of life. To achieve the objectives of the current research, two scales were adopted, the first to identify self-destruction and the second for mental disorders. The research sample consisted of (200) male and female students. The current research has concluded that there is a statistically significant correlation between self-destruction and mental disorders, but there are no differences in the relationship according to gender and specialization. The current research has reached a number of proposals and recommendations.